UJI AKTIVITAS ANTIOKSIDAN METODE DPPH DARI EKSTRAK ETANOL DAUN SUKUN (Artocarpus altilis L.) MENGGUNAKAN METODE MASERASI - Cindy Kurnia Sari; Razoki Razoki; Erida Novriani (JIFI (Jurnal Ilmiah Farmasi Imelda), 2026)
Breadfruit leaves (Artocarpus altilis L.) area plant with various health benefits due to their natural chemical compounds, one of which acts as an antioxidant. Antioxidants are compounds that can halt the oxidation process by donating electrons, there by protecting normal cells, fats, and proteins from damage caused by free radicals. The concentration of an antioxidant that causes a 50% reduction in DPPH activity is referred to as the IC50.  The objective of this study was to determine the effectiveness of ethanol extract from breadfruit leaves in combating oxidation using the DPPH method. The results showed an IC50 value of 6.66 ppm for the extract, indicating very strong antioxidant activity, although it was more effective compared to vitamin C, which served as a positive control with an IC50 value of 1.15 ppm. This difference in effectiveness is influenced by the amount of phenolic compounds present and the potential pro-oxidant effects at higher concentrations. In summary, breadfruit leaves have high potential as asource of natural antioxidants and can be used to develop pharmaceutical products to treat degenerative diseases.